Resistance to recombinant human erythropoietin therapy in haemodialysis patients: Focus on inflammatory cytokines, leukocyte activation, iron status and erythrocyte damage - Costa, Elísio (2010)
Anaemia is a common complication in haemodialysis patients. This condition is associated to a decreased bone marrow production of erythrocytes, mainly due to the inability of the failing kidneys to secrete erythropoietin (EPO). The introduction of recombinant human EPO (rhEPO) therapy led to a significant reduction in anaemia and improved patients’ quality of life. However, there is a marked variability in the sensitivity to rhEPO, with up to 10-fold variability in dose requirements to achieve correction of anaemia. Approximately 5-10% of the patients show a marked resistance to rhEPO therapy. rhEPO resistance is associated to an increased morbidity and mortality of haemodialysis patients. In this paper a revision of the mechanisms underlying resistance to rhEPO therapy will be performed, with particular emphasis on inflammatory cytokines, leukocyte activation, iron status, and erythrocyte damage.